„Rószczką czarodziejską w świat marzeń”. Przewodnik Walerego Eljasza i jego znaczenie w rozwoju turystyki tatrzańskiej - Opaliński, Dariusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
Artykuł poświęcony jest przewodnikowi tatrzańskiemu Walerego Eljasza, który począwszy od roku 1870, w odstępach kilkuletnich, był wznawiany przez kolejne trzydzieści lat. Była to lektura niezmiernie ważna dla kształtowania świadomości Polaków o tych górach w okresie zaborów. Autor przewodnika był człowiekiem wszechstronnie utalentowanym. Zajmowało go malarstwo, grafika, fotografika, pisarstwo i turystyka. Te dwie ostatnie pasje (ale także grafikę) udanie połączył w swych przewodnikach. Artykuł jest próbą oceny zawartości kolejnych wydań przewodnika i określenia znaczenia tego tekstu dla rozwoju szeroko rozumianej masowej turystyki tatrzańskiej drugiej połowy XIX w.

The article is devoted to Walery Eljasz’s Tatra guides, which, starting in 1870, were reissued at several-year intervals over the next thirty years. These works were extremely important in shaping Polish awareness of the Tatra Mountains during the period of the partitions. The author was a versatile talent, interested in painting, graphic arts, photography, writing, and tourism. He successfully combined his last two passions (and also graphic arts) in his guides. The article attempts to evaluate the contents of successive editions of the guides and to determine their significance for the development of broadly understood mass tourism in the Tatra region in the second half of the 19th century.
“With a Magic Rod into the World of Dreams”: Walery Eljasz’s Guides and Their Significance in the Development of Tatra Tourism
Keywords: Walery Eljasz; przewodniki tatrzańskie; turystyka tatrzańska XIX w.; polskie przewodnikopisarstwo; Tatra guides; 19th-century Tatra tourism; Polish guidebooks; historical geography